Growth and fruit body formation of Pleurotus ostreatus on media supplemented with inorganic selenium - Savić Milena D.; Petrović Jelena P.; Klaus Anita S.; Nikšić Miomir P.; Rajković Miloš B.; Filipović Nenad R.; Antić-Mladenović Svetlana B. (Zbornik Matice Srpske za Prirodne Nauke, 2009)
Selenium is a trace mineral chemically related to sulfur and tellurium. In the body selenium combines with protein molecules to form selenoproteins and it is distributed in low concentrations and unequally in air, soil and water all over the world. Edible mushrooms are known to be selenium accumulators. Since mushrooms contain relatively high protein levels, and they can accumulate large amounts of selenium, it is reasonable to expect that selenium could be incorporated into proteins. The growth of mycelia and fruit body formation of different medicinal mushroom strains of Pleurotus ostreatus (Hk-35 and P70) over the wide range of concentrations of inorganic form of selenium were examined. Mushrooms were cultivated on agar base media and on substrates based on sawdust. Vegetative growths of mycelium were measured as colony diameter in pure cultures supplemented with inorganic form of Se supplements, prepared as Na2SeO4 and Na2SeO3 in concentrations of: 1, 10, 25, 50, 75, 100 and 150 mg/l. Inorganic form of Se supplements, showed stimulation effects (in concentration of 1-50 mg/l) and toxic effects in higher concentration. On the standard industrial sawdust based substrate, supplemented with 100 mg/kg Na2SeO4 and Na2SeO3, accumulation of Se in fruit bodies was determined by the method of flameless atomic absorption spectrophotometer. The readings were performed on Varian SpectrAA-10 spectrophotometer equipped with VGA-76. Se as Na2SeO4 and Na2SeO3 was effectively taken up from substrates and accumulated in fruit bodies. Mushrooms accumulated selenium between 120 and 250 mg/kg dry weight. In mushrooms cultivated without Se supplement, Se contents were only about 1 mg/kg and in substrate about 0.1 mg/kg.